Reasons for doctor migration from South Africa - Marlene M. Bezuidenhout; Gina Joubert; Louis A. Hiemstra; Magdalena C. Struwig (South African Family Practice)
Background: The migration of doctors from their home countries is not a new phenomenon. Apart from voluntary migration due to various reasons, medical professionals, often from sub-Saharan Africa, are actively recruited by developed countries. Doctors in South Africa are esteemed for the high standard of training they receive locally, a quality which renders them prime candidates for employment. Various factors are involved in the push-pull theory of migration. It has, however, been reported extensively that push factors usually play a much greater role in doctors’ decision to leave their countries of origin, than do pull factors in the host or recipient country. Push factors motivating migration most frequently include dissatisfaction with remuneration packages and working conditions, high levels of crime and violence, political instability, lack of future prospects, HIV/AIDS and a decline in education systems. In addition to a depletion of intellectual resources through losing highly qualified and skilled individuals, source countries also face substantial monetary implications caused by the migration of doctors. Government subsidy of medical students’ training could be regarded as a lost investment when young graduates seek permanent employment abroad. The aim of the study was to investigate the profile of South African qualified physicians who had emigrated from South Africa.